Temporal Variation of Airborne Dust Concentrations in the Mogao Grottoes, Dunhuang, China - Zhang, Guobin; Tan, Lihai; Zhang, Weimin; Zhan, Hongtao; Qiu, Fei (Frontiers in Environmental Science, 2022)
Dust storms bring a large quantity of dust aerosols from arid and semi-arid regions of the Earth. However, real-time dust concentration data for dust storms in arid regions, important for wind erosion studies, are still limited. Here, temporal variation of airborne dust concentrations in the Mogao Grottoes, Northwest China, during the monitoring period from February to October, 2012 and typical dust storms under different wind directions were analyzed. Results reveal that the monthly mean total suspended particle (TSP), particulate matter less than 10 μm (PM10), and particulate matter less than 2.5 μm (PM2.5) concentrations gradually decreased from February to October. The daily mean dust concentrations fluctuated with the day, with extreme values occurring mainly on February, March, and April. The daily mean PM10/TSP ratio ranged from 0.67 to 0.98 (mean of 0.82), and the PM2.5/PM10 ratio ranged from 0.31 to 0.73 (mean of 0.55), indicating PM10 dominated in TSP. In typical dust storms, the maximum real-time concentrations can reach 16, 000-21, 000 μg TSP m-3, ~11, 000 μg PM10 m-3, and 3000-3500 μg PM2.5 m-3, and extreme real-time dust concentrations of 50358.03 μg TSP m-3, 33100.86 μg PM10 m-3, and 7502.59 μg PM2.5 m-3 were recorded. Coincidence of the dry climate and windy season and sufficient dust sources in the surrounding environment contributed to the high dust concentrations in the Mogao Grottoes. To achieve the goal of minimizing the damage of falling dust to the murals and statues, establishing a dust storm early warning system and improving the existing sand control system are recommended.